Determinasi Digital Payment, Persepsi Konsumen, Kualitas Pelayanan Dan Lokasi Terhadap Keputusan Pembelian Dimediasi Minat Beli Pada Cv Sido Makmur Di Babat Lamongan - Maria Laimu; Abid Muhtarom; Danu Kusbandono (Jurnal Penelitian Teori & Terapan Akuntansi (PETA), 2023)
The business world is currently growing rapidly, this causes entrepreneurs to have to face fierce competition in the business world. Bicycles are vehicles that are in great demand from various circles. The novelty in this study is 6 variables, namely Digital Payment, Consumer Perception, Service Quality, Location, Purchase Decision and Purchase Interest, as well as research locations that have never been studied. This type of quantitative descriptive research, the sample used as many as 240 samples using simple random sampling technique. The test tool uses Smasrt PLS version 3.0. The research result it can be concluded that Digital Payment (X1), Consumer Perceptions (X2), Service Quality (X3), Location (X4) have a positive and significant effect on Purchase Decision (Y). In the digital payment variable mediation test, consumer perceptions of purchase decisions mediated by purchase intention is said to be Non Mediation, theevariableeservice quality, location onnpurchase decisions mediated by purchase intention is said to be Partial Mediation.